Larviciding for malaria control and elimination in Africa - Gretchen Newby; Prosper Chaki; Mark Latham; Dulcisária Marrenjo; Eric Ochomo; Derric Nimmo; Edward Thomsen; Allison Tatarsky; Elijah O. Juma; Michael Macdonald (Malaria Journal)
Abstract Background Global progress toward malaria elimination and eradication goals has stagnated in recent years, with many African countries reporting increases in malaria morbidity and mortality. Insecticide-treated nets and indoor residual spraying are effective, but the emergence and increased intensity of insecticide resistance and the challenge of outdoor transmission are undermining their impact. New tools are needed to get back on track towards global targets. This Perspective explores the major challenges hindering wider-scale implementation of larviciding in Africa and identifies potential solutions and opportunities to overcome these barriers. Larviciding in Africa: overview, challenges, and solutions Larviciding is a valuable vector control tool with strong potential for regional scale-up. There is considerable evidence of its effectiveness, and the World Health Organization (WHO) recommends it as a supplemental intervention. However, malaria programmes hoping to implement larviciding face significant barriers, including (1) poor global technical, policy, and funding support; (2) fragmented implementation and experience; (3) high complexity of delivery and impact evaluation; and (4) limited access to the full range of WHO prequalified larvicide products. Strategic barriers related to global policy and donor hesitancy can be overcome through a coordinated demonstration of cost-effectiveness. Technological advancements and strengthened operational capacity have already overcome technical barriers related to larvicide delivery, targeting, coverage, and evaluation. Developing a Community of Practice platform for larviciding has strong potential to consolidate efforts, addressing the challenge of fragmented implementation and experience. Such a platform can serve as a resource center for African malaria programmes, collating and disseminating technical guidance, facilitating the exchange of best practices, and aiding malaria programmes and partners in designing and evaluating larviciding projects. Conclusion The global shift toward targeted and adaptive interventions enables the incorporation of larviciding into an expanded vector control toolbox. As more African countries implement larvicide programmes, establishing a regional Community of Practice platform for exchanging experiences and best practices is necessary to strengthen the evidence base for cost-effective implementation, advocate for support, and inform policy recommendations, thus supporting Africa’s progress toward malaria elimination.